Zilucoplan in immune-mediated necrotising myopathy: a phase 2, randomised, double-blind, placebo-controlled, multicentre trial. (February 2023) - Mammen, Andrew L; Amato, Anthony A; Dimachkie, Mazen M; Chinoy, Hector; Hussain, Yessar; Lilleker, James B; Pinal-Fernandez, Iago; Allenbach, Yves; Boroojerdi, Babak; Vanderkelen, Mark; Delicha, Eumorphia Maria; Koendgen, Harold; et al.
Summary: Background: Immune-mediated necrotising myopathy is an autoimmune myopathy characterised by proximal muscle weakness, high creatine kinase concentrations, and autoantibodies recognising 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR) or the signal recognition particle (SRP). No approved therapies exist for people with immune-mediated necrotising myopathy. Previous studies have suggested that complement activation might be pathogenic in immune-mediated necrotising myopathy; therefore, zilucoplan, a complement C5 (C5) inhibitor, could be a potential therapy. We aimed to evaluate the efficacy, safety, and tolerability of zilucoplan in adult participants with anti-HMGCR or anti-SRP autoantibody-positive immune-mediated necrotising myopathy. Methods: IMNM-01 was a phase 2, multicentre, randomised, double-blind, placebo-controlled study done at 15 hospital sites across the USA, the UK, France, and the Netherlands. Participants aged 18–74 years were eligible for inclusion if they had a clinically confirmed diagnosis of immune-mediated necrotising myopathy, positive serology for anti-HMGCR or anti-SRP autoantibodies, clinical evidence of weakness, serum total creatine kinase concentration of more than 1000 U/L at screening, and no change in glucocorticoids or other immunosuppressive therapies for 30 days before baseline or expected during the first 8 weeks of the study. Participants were randomly assigned (1:1) to receive daily subcutaneous zilucoplan (0·3 mg/kg) or placebo for 8 weeks by use of a computerised randomisation algorithm; with optional enrolment in the study open-label extension. Randomisation was stratified by autoantibody status. Participants and study staff were masked to treatment group assignment. Primary efficacy endpoint (in the intent-to-treat population, defined as all participants who were randomly assigned to a treatment group) was percent change from baseline to week 8 in creatine kinase concentrations. Safety analyses were performed on the safety population (participants who received at least one dose of study drug during the main study, irrespective of whether they continued to the extension period—study participants were analysed on the basis of the treatment received). This study is registered with ClinicalTrials.gov, NCT04025632 . Findings: Between Nov 7, 2019, and Jan 7, 2021, we randomly assigned 27 participants (13 female and 14 male) to receive zilucoplan (n=12) or placebo (n=15). All 27 participants completed the 8-week main study. At week 8 there were no significant differences between treatment groups in median percent change of creatine kinase concentrations versus baseline (–15·1% [IQR –31·1 to 3·2] in the zilucoplan group vs –16·3% [–43·8 to 5·9] in the placebo group; p=0·46) and no clinically relevant improvement over time within the treatment group despite target engagement based on mode of action. There were no unexpected adverse safety or tolerability findings. Treatment-emergent adverse events were reported in nine (75%) of 12 participants in the zilucoplan group, and in 13 (87%) of 15 participants in the placebo group, and serious treatment-emergent adverse events were reported in zero participants in the zilucoplan group and three (20%) participants in the placebo group. The most frequent treatment-emergent adverse events were headache (four [33%] participants in the zilucoplan group and four [27%] participants in the placebo group) and nausea (three [25%] participants in the zilucoplan group and three [20%] participants in the placebo group). Interpretation: C5 inhibition does not appear to be an efficacious treatment modality for people with immune-mediated necrotising myopathy. Rather than being the primary driver for disease activity, complement activation might be secondary to muscle injury. Funding: Ra Pharmaceuticals (now part of UCB Pharma).